(untitled) (Simbiótica. Revista Eletrônica, 2024)
This text provides an overview of the discussions provoked by the return of the subject of Sociology to the school curriculum in 2008 and presents the texts in this dossier dedicated to the theme. The return of Sociology as a compulsory subject in high school sparked a new round of discussion about the role of Sociology in basic education, specific teaching methodologies, the teacher profile, the experiences resulting from the work of institutional programs aimed at teacher training and their impact on undergraduate degrees in Social Sciences, as well as reflections on the position of Sociology in the face of recent changes in the organization and curriculum brought about by the High School Reform and the Common National Curriculum Base. These and other themes, and their various tensions, are present in the data and analysis offered by the authors of the articles in this dossier on sociology teaching.